The STEM problem-based inquiry learning for diffusion and osmosis concepts / Usman Gado Birnin Tudu, Mohd Norawi Ali and Mohammad Zohir Ahmad - Gado Birnin Tudu, Usman; Ali, Mohd Norawi; Ahmad, Mohammad Zohir (Universiti Teknologi MARA, Cawangan Melaka, 2023)
Without proper and efficient learning methodologies, educational achievement cannot be of high quality. Modular teaching and learning have reportedly been shown to boost students' academic performance. The purpose of this paper was to develop STEM Problem-based inquiry module for learning diffusion and osmosis concepts for form four biology students at secondary school level in Nigeria. This study is significant for the curriculum planners, education policy-makers, and biology teachers on how to develop learning module. Several studies have continued to report students' poor performance in biology due to ineffective teaching strategy employed by teachers. The paper also highlights some instructional design models and selects the design guidelines of the ADDIE instructional model. The researchers utilised purposive sampling to select the subjects. The Fuzzy Delphi Method (FDM) was used to determine the experts who would validate this module. Experienced biology teachers (n = 15) are provided with a checklist questionnaire for validation purposes. The validation of the module yielded the S-CVI of 0.86. The developed module revealed that it is suitable and appropriate for biology students' learning of diffusion and osmosis concepts. Additionally, the findings of this study suggest that the ADDIE instructional design model is the best choice for creating modular teaching approaches at secondary educational setting.